The Effect of Project-Based STEAM Acquire on Student Creativity in Science Learning During the Pandemic Period - Dewi Suliyanthini; Fajar Yulianur (Postgraduate, University of Mataram, 2023)
The reason for this think about was to look at the impact of Project-based STEAM acquisition on college inventive considering and basic considering aptitudes. The ponder utilized a quasi-experimental plan using a nonequivalent pretest-posttest control gather plan. The populace for ponder were all understudies in Sunan Ampel State Islamic University, Surabaya whereas the test utilized included one department of Biology for the test course and one department of Engineering, utilized as the control lesson. The purpose of this study is to provide an overview in the form of a description of the implementation of STEAM-based acquisition for children aged 5-6 years at Al-Azhar Syifa Budi Surakarta Kindergarten. The information collected was at that point analyzed utilizing the ANOVA test. The pjBL-based STEAM acquisition had a critical impact on understudies’ imaginative considering abilities (P 0.000 < 0.005; Fcount = 25.551). The pjBL-Based STEAM acquisition had a critical impact on understudies’ basic considering aptitudes (P 0.003<0.05, Fcount=9,401). So, PjBL-Based STEAM acquire can be utilized as elective acquire to enable 21st-century abilities.